Clotting Problems with the Teflon-Silastic Arteriovenous Shunt in Patients on Regular Haemodialysis. Issue 5648 (5th April 1969) - Papadimitriou, M.; Carroll, R. N. P.; Kulatilake, A. E.
Abstract : Episodes of clotting that occurred in 22 patients on regular haemodialysis were studied over a six-month period. The venous pressure during dialysis and the radiology of the Teflon-Silastic arteriovenous shunt were found to be satisfactory guides for the management of the shunt. The failure of the shunt during the early stage was mainly due to technical reasons. Histological study of the excised vessels in removed long-term shunts showed that these had failed because of rigidity and thickening of the vessel wall due to calcium and iron deposits or chronic inflammation, or both.